If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 + 4x + 4x + 5 = 4x + 4x + 5x + 5 Reorder the terms: 6 + 5 + 4x + 4x + 4x = 4x + 4x + 5x + 5 Combine like terms: 6 + 5 = 11 11 + 4x + 4x + 4x = 4x + 4x + 5x + 5 Combine like terms: 4x + 4x = 8x 11 + 8x + 4x = 4x + 4x + 5x + 5 Combine like terms: 8x + 4x = 12x 11 + 12x = 4x + 4x + 5x + 5 Reorder the terms: 11 + 12x = 5 + 4x + 4x + 5x Combine like terms: 4x + 4x = 8x 11 + 12x = 5 + 8x + 5x Combine like terms: 8x + 5x = 13x 11 + 12x = 5 + 13x Solving 11 + 12x = 5 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 11 + 12x + -13x = 5 + 13x + -13x Combine like terms: 12x + -13x = -1x 11 + -1x = 5 + 13x + -13x Combine like terms: 13x + -13x = 0 11 + -1x = 5 + 0 11 + -1x = 5 Add '-11' to each side of the equation. 11 + -11 + -1x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 5 + -11 -1x = 5 + -11 Combine like terms: 5 + -11 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 2(x-24)+4(x-3)=36 | | 2x+13=91 | | 7=3p-8 | | 19-13p=-17p-8 | | -35=-7+-6a | | 9v+2v-14v+8q= | | 9+5v=2v-9 | | 0=x^2-64x-512 | | 5+-(8)n=29 | | 21+2n=43 | | -164=-5-3(7m+4) | | cos(x)-cos(7x)=sen(4x) | | 6(2x-3)-13=2(x-1) | | 3=2b+5b | | 5(3y-11)=-10 | | 3y+27=6x | | x+(x+0.39)+(x+0.41)=10.25 | | -4y=12y-64 | | 4+-2g=16 | | 19-5x-8+7x= | | -7-14=35 | | 16-16x-x^2=4x+5 | | 52=3w+13 | | 3=-3(x+10) | | 5x+4x-45=60-6x | | 5y+y=48 | | 1x-.30x=525 | | 16t-t-5s-9t= | | -18.99=x+6.23 | | 9w-w=48 | | 4x+3x=15 | | 15i-4f-17i+3f= |